Technical Perspective: THE DATA CENTER IS THE COMPUTER. - Patterson, David A. (Communications of the ACM, 2008)
The article discusses MapReduce, a scheme developed by Google for managing the workloads for data center computers. A data center is apt of have a wide variety of machines with differing capacities. MapReduce addresses this by making assignments based on how efficiently a machine has completed recent work. Particularly slow machines will have incomplete workloads reassigned to faster machines. The program also makes allowances for hardware failure. MapReduce is simple enough for even novice programmer to use.